A displacement approach for competitive drug-protein binding studies using the potentiometric 1-anilino-8-naphthalene-sulfonate probe technique - Angelakou, A; Valsami, G.; Macheras, P.; Koupparis, M. (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 1999)
A displacement approach for competitive binding studies was developed. The method utilizes the potentiometric 1-anilino-8-naphthalene-sulfonate (ANS) probe technique and is applied to the binding study of several non-steroidal anti-inflammatory drugs (NSADs) to bovine serum albumin (BSA). A home-made ANS electrode was used to monitor the displaced free ANS probe from its binding sites on the protein molecule by the stepwise addition of the studied drug. To assess and compare quantitatively the displacing ability of the various drugs, the `ANS Displacement Index' is used. The possible interference of 19 ionizable drugs (NSADs, sulfonamides, etc.) to the ANS selective electrode at pH 7.4 was studied and their potentiometric selectivity coefficients (K-ANS,D(pot)) were determined. Correction procedures for the determination of the free ANS concentration are proposed in the case of interfering ionic drugs. A blank binding experiment in conjunction with the incorporation of K-ANS,D(pot) values in the `general competitive site oriented model' allows one to derive estimates for the drug binding parameters, i.e. the number of binding sites and association constants. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: 1-anilino-8-naphthalene-sulphonate; ion selective electrodes; non-steroidal anti-inflammatory drugs; potentiometric probe technique; potentiometric selectivity coefficient; Protein Binding